Basura [videorecording] saw it coming ... - Severino, Howie; Philippine Center fir Investigative Journalism (Quezon City GMA News and Public Affairs, 2000)
Garbage is not a simple problem. for metropolis of 10 million people, it has become an environmental, political and economic issue.
Hosted by award winning environmental journalist Howie Severino, Basura or Garbage examines Metro Manila's perenial problem, now worsening as yhe population increases and the economy grows. It also affers solution, citing communities where garbage is recycled or transformed into compost right in their own areas.
July 10, 2000 a mountain of trash buried a community of scavengers in Payatas, Quezon City, killing over two hundred people. This is how garbage kills.
Producer: GMA News and Public Affairs; Line Producer: PCIJ; Reporter/Scriptwriter: Howie Severino; Supervising Producer: Oweb Santos; Cameraman: Egay Navarro
Keywords: Scavenger -- Life; Garbage